THE INFLUENCE OF WORK ENVIRONMENT AND WORKLOAD ON EMPLOYEE PRODUCTIVITY AT SALOBULO PUBLIC HEALTH CENTER, SAJOANGING DISTRICT, WAJO REGENCY - Mita Dewi Asmara; Anwar Ramli; M. Ikhwan Maulana Haeruddin; Uhud Darmawan Natsir; Tenri Sayu Puspitaningsih Dipoatmodjo (Adisam Publisher, 2025)
This study aims to determine the influence of work environment and workload on employee productivity at the Salobulo Public Health Center, Sajoanging District, Wajo Regency. The background of this research is based on the importance of a quality work environment and effective workload management in supporting the effectiveness and efficiency of employee performance, particularly in the health service sector. The method used in this research is a quantitative method with a descriptive associative approach. Data collection techniques include observation, interviews, documentation, and the distribution of questionnaires to 43 employees of the health center, selected using a saturated sampling technique. The results of the study indicate that, partially, the work environment has a positive and significant influence on employee productivity. This is demonstrated by the comfort of the workspace, harmonious relationships among colleagues, and support from superiors. Workload also affects employee productivity, as some employees experienced an imbalance in task distribution and fatigue due to additional responsibilities beyond their main duties. Simultaneously, the work environment and workload have a significant effect on employee productivity. Therefore, improving employee productivity requires better management of the work environment and a more proportional distribution of workload. This research is expected to serve as a reference for the health center in formulating policies related to human resource management and as a foundation for future researchers in developing studies related to factors that influence employee productivity in the health service sector.